1999
DOI: 10.1007/s002689900627
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation: A Global Bug That Should Not Cross the Millennium Bridge

Abstract: Female genital mutilation (FGM) has been practiced worldwide, clothed under the tradocultural term "circumcision." Indications for its practice include ensuring virginity, securing fertility, securing the economic and social future of daughters, preventing the clitoris from growing long like the penis, and purely as a "tradition." Outlawed only in the United Kingdom, Sweden, and Belgium, no law forbids it in most other countries. Classified into four identified types, the current perpetrators are mainly quacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…Several epidemiological studies also linked bleeding and severe pain resulting from FGC with common health complications (see, for example, Eke andNganginieme, 1999:1082-83;El-Shawarby and Rymer, 2008:254;WHO, 2008:11).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies also linked bleeding and severe pain resulting from FGC with common health complications (see, for example, Eke andNganginieme, 1999:1082-83;El-Shawarby and Rymer, 2008:254;WHO, 2008:11).…”
Section: Discussionmentioning
confidence: 99%
“…The acquired causes may be iatrogenic including female genital mutation or circumcision4 – 6 and vaginal reconstructive surgeries7 resulting in painful keloid formation, labial adhesions and vulval disfigurement,5 , 6 vulval disease such as lichen sclerosis,8 psychosexual problems leading to vaginismus (often associated with a history of sexual abuse, trauma or rape), or as a result of malunion of stress and insufficiency pelvic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that upto 12% of FGM are performed by medical doctors with sophisticated and sterile medical equipment in hospitals and clinics. Furthermore some of the earliest practitioners of FGM included doctors from USA and Great Britain, and a physician was deregistered in Britain only in 1993 for performing illegal FGM operations (12,15).…”
Section: Surgeons' Who Perform Fgmmentioning
confidence: 99%
“…In 1978 in Somalia, a commission was set up to abolish infibulation but its recommendations were not enforced (4,46). Over the years, the enormity of the FGM ritual has occasionally been brought to sharp focus although this attention has not been sustained (4,12). The World Health Organisation (WHO) has since 1982 consistently stated its displeasure with the health care professionals and other unqualified circumcisers involved in the practice of female genital mutilation (circumcision).…”
Section: Global Efforts and Legislation To End Fgmmentioning
confidence: 99%
See 1 more Smart Citation